A MEASURE OF THE EFFECT OF COMPLEX FOOD ADDITIVES ON RATS’ ADAPTIVE RESPONSES - Yachmin, А.І.; Kononov, B.S.; Yeroshenko, G.А.; Bilash, S.М.; Bilash, V.P. (World of Medicine and Biology, 2020)
In the paper was the investigation of the effect of consumed complex food additives on the rats’ adaptive response. 88 outbred mature male rats, housed in the common conditions, were involved into the study. Control rats consumed drinking water and received saline per os. The rats of the experimental group were given ad libitum access to water and, supplementary, consumed sodium nitrite solution. Sodium glutamate was administered at a dose of 20 mg/kg, Ponceau 4R at a dose of 5 mg/kg once daily per os. Doses of food additives were half less the allowable normal rate in food. After being exposed to open field test the rats were killed within 1, 4, 8, 12 and 16 weeks under thiopentone anesthesia overdose. Consumption of complex food additives at acceptable doses affects the behavioral responses of experimental animals. It has been established that just from the first week of observation, rats experienced increased anxiety, fear, blunting of adaptive responses, decreased activity and disturbance of the emotional state, which were intensified up to week 16 of the experiment.
Keywords: open field test; sodium nitrite solution; sodium glutamate; Ponceau 4R; adaptive-locomotor behavior of rats